CD95 promotes metastatic spread via Sck in pancreatic ductal adenocarcinoma - Teodorczyk, Marcin; Weichert, Wilko; Bergmann, Frank; Welsch, Thilo (Cell death and differentiation, 2015)
Cancer stem cells (CSCs) have been implicated in the initiation and maintenance of tumour growth as well as metastasis. Recent reports link stemness to epithelial-mesenchymal transition (EMT) in cancer. However, there is still little knowledge about the molecular markers of those events. In silico analysis of RNA profiles of 36 pancreatic ductal adenocarcinomas (PDAC) reveals an association of the expression of CD95 with EMT and stemness that was validated in CSCs isolated from PDAC surgical specimens. CD95 expression was also higher in metastatic pancreatic cells than in primary PDAC. Pharmacological inhibition of CD95 activity reduced PDAC growth and metastasis in CSC-derived xenografts and in a murine syngeneic model. On the mechanistic level, Sck was identified as a novel molecule indispensable for CD95’s induction of cell cycle progression. This study uncovers CD95 as a marker of EMT and stemness in PDAC. It also addresses the molecular mechanism by which CD95 drives tumour growth and opens tantalizing therapeutic possibilities in PDAC.
Gesehen am 30.06.2020